Correlation between ADR of screening and all colonoscopies - Mikoviny Kajzrlikova, Ivana; Vitek, Petr; Chalupa, Josef; Kuchar, Jan; Platos, Jiri; Reha, Pavel; Klvana, Pavel (Biomedical papers, 2021)
Background and Aims. Colonoscopy with polypectomy are associated with a reduction in the incidence of colorectal cancer (CRC), as well as mortality, secondary to CRC. Because of the variation in physicians' performance and the risk of interval CRC after a colonoscopy, several quality indicators have been established. ADR (adenoma detection rate) is a generally accepted quality indicator. But it is also a target of possible gaming and achieving an adequate number of colonoscopies only from screening may be a problem for some practices. The aim of this study was to compare ADR for colonoscopies done for various indications and to look for correlations between the ADR of screening and all examinations. Methods. We retrospectively assessed the quality indicators of all colonoscopies performed in a nonuniversity hospital, Frydek-Mistek, from January 2013 to December 2017. We calculated the ADR for all colonoscopies in patients over 50 years of age (subdivided into screening, surveillance, diagnostic) and separately only for screening colonoscopies. Correlations were made using the Pearson's correlation coeficient. Results. The sample was composed of 6925 patients over 50 years of age (3620 men, 3305 women, mean age 66.2 years). The ADRs for screening and surveillance were higher than for diagnostic colonoscopies for all of the endoscopists, and the ADRs for all colonoscopies were lower than for screening, but sufficiently over 25%. There was a positive correlation between the ADR of screening and all colonoscopies (r=0.906, P<0.005). Conclusions. The calculation of ADR for all colonoscopies was possible in our endoscopic department, and there was a positive correlation with ADR for screening colonoscopies. ADR for all colonoscopies is a good tool for calculating real ADR from large sample sizes without gaming. Trial Registration: ClinicalTrials.gov (NCT03730441).
Keywords: adenoma; colorectal neoplasms; colonoscopy; quality improvement; standards; screening